Digital Signal Processing for Directly Modulated Lasers in Optical Fiber Communications - Karar, Abdullah S. (2013)
Thesis (Ph.D, Electrical & Computer Engineering) -- Queen's University, 2013-01-31 13:58:56.327 Directly modulated lasers (DMLs) are a low cost solution for moderate reach systems due to their small footprint, low power dissipation and high output optical power. However, commercial 10-Gb/s on-off keying DMLs have been limited by an inherent modulation of the optical phase that accompanies the desired modulation of the optical intensity, which reduces their transmission distance to below 20 km. Furthermore, the ability to generate bit rates beyond 10-Gb/s with advanced modulation formats has been limited by the strict requirements on the laser drive current. The primary objective of this research is to dramatically enhance the capability of DML based systems through precise control over the drive current. This is achieved by digital signal processing (DSP) combined with a single digital-to-analog converter (DAC). In this research, a novel method to pre-compensate dispersion for metro and regional networks is demonstrated at 10.709-Gb/s. A look-up table (LUT) for the driving current is optimized for dispersion mitigation. Experimental results show a 25 fold increase in the transmission reach of a DML from 10 km to 252 km. A similar approach applied to a directly modulated chirp managed laser reveals a remarkable increase in the achievable transmission reach from 200 km to 608 km. In the context of access networks the DSP and DAC configuration is utilized for directly modulating a passive feedback laser (PFL) to generate differential phase shift keying (DPSK) signals at bit rates of 10.709-Gb/s, 14-Gb/s and 16-Gb/s. The quality of the DPSK signals is assessed using both noncoherent detection for a bit rate of 10.709-Gb/s and coherent detection with DSP involving a LUT pattern-dependent distortion compensator. For very short reach optical links, a 16-ary quadrature amplitude modulation signal is generated using subcarrier modulation with a subcarrier frequency of half the symbol rate, Nyquist pulse shaping, ...